It is a matter of how you say it: Verbal content and prosody matching as an index of emotion regulation strategies during the Adult Attachment Interview. (7th February 2017) - Spinelli, Maria; Fasolo, Mirco; Coppola, Gabrielle; Aureli, Tiziana
Abstract : Emotional activation can be detected by the prosodic properties of the voice. This study aimed to explore the match between the valence of the words used by secure and dismissing women in describing the relationship with their parents during the Adult Attachment Interview and their emotional activation as expressed through the prosody of the voice. Contrary to what observed for secure women, a discrepancy emerged in dismissing individuals between the content of their verbal reports during the interview and the emotional activation of their voice while speaking. Negative experiences, usually cognitively minimised and normalised, were expressed with high emotional arousal, while positive descriptors, often exaggerated semantically, were expressed with neutral arousal. Therefore, the defensive inhibition strategy seems to control the content but not the prosody of narratives and prosody has the potential to allow a better understanding of the emotion regulation strategies used by individuals while discussing their caregiving histories.